EFEK TEKANAN AWAL DRIVER SECTION TERHADAP KARAKTERISTIK GELOMBANG DETONASI PADA KONDISI INISIASI LANGSU - , ESWANTO,ST; , Dr. Eng. Jayan Sentanuhady, ST., M.Eng., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The process of detonation wave propagation from deflagration to detonation occurrence can not be separated from the influence of initial pressure in driver section starting reaction mixture of fuel combustion and oxidizer. Success do not it the process combustion fuel mixture gas into the detonation wave strongly influenced by the concentration of gases in mixture and also the pressure gas mixture. The on one hand use fuel gas for industrial and domestic purposes in the future will increase. This research objective to study the characteristic fuel mixture (H2 - O2, H2 - air, LPG - O2, LPG - air) due to influence of initial pressure on the driver section in detonation test tube to the possibility of detonation wave. The equipment used is detonation test tube with 6000 mm length and 50 mm diameter. The increase in pressure shock wave was observed with four pressure sensors unit, while the arrival time flame front by four units of detection probes mounted on the contrary detonation test tube. Detonation wave recorded with soot track record aims to find traces of the detonation wave and detonation cell size. Fuel mixture is used on the driver section is stoichiometric hydrogenoxygen mixture at initial pressure is conditioned by variable pressure 20-100 kPa with intervals of 10 kPa at room temperature. As for the driven section use mixed fuel (H2 - O2, H2 - air, LPG - O2, LPG - air) with initial pressure 100 kPa. From the results this study indicate that initiation directly in driver section can significantly affect propagation detonation wave in the driven section. In the upstream region driven section it appears detonation wave is still not stable, as seen in the soot track record of detonation cell size not the same size, the stable detonation wave is visible only when combustion wave has passed through the area downstream of driven section, the condition can be seen from the recording soot track record with detonation cell size is relatively constant. Increasing the initial pressure of mixture can shorten distance the deflagration to detonation transition (DDT) from the ignition point and will reduce detonation cell size width due to higher combustion reaction. The increase in pressure highest in the LPG-O2 mixture is 3144.6 kPa or 31.45 times the initial pressure with DDT distance 1060 mm from the ignition point and detonation cell width Î» = 1.14 mm, detonation cell size gets smaller if the initial pressure initiation increases.